Design And Development Of GP-Based Data Mining Systems - Lim, Amy Hui Lan (2003)
Initially, function using genetic programming (GP) is investigated through symbolic regression for data mining applications. Various kinds of functions are investigated including function learning tasks as well as Boolean functions learning. The objective of the initial investigation is to review how GP is applied to function learning tasks. The drawbacks of this method are identified.